Primitive trigeminal artery associated with aterovenous malformation of cerebellum - Jovanović Igor B.; Samardžić Miroslav; Nagulić Mirjana; Baščarević Vladimir; Mićović Mirko; Milošević Svetlana (Vojnosanitetski Pregled)
Introduction. Persistence of fetal cerebral carotid basilar anastomoses is rare. When it occurs, it is often associated with other vascular malformations, and other pathological conditions. Trigeminal primitive artery persistence is the most often among them. Coincidence of primitive trigeminal artery with cerebellar arteriovenous malformation is extremely rare. Case report. We reported a case of a 31-year-old woman with subarachnoid hemorrhage and cerebellar hematoma admitted in serious condition. Angiography demonstrated cerebellar arteriovenous malformation, primitive trigeminal artery and other malformation of Willis circle. After a complete surgical removal of arteriovenous malformation the patient was discharged without neurological or any other deficit. Conclusion. We reported an extremely rare condition, which had been reported very few times in the literature. The importance of primitive artery persistence is in changed anatomical and physiological condition of cerebral circulation, that is especially important in surgical procedures.